2000
DOI: 10.1097/00007632-200002150-00014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Transligamentous Extension of Lumbar Disc Herniations on Their Regression and the Clinical Outcome of Sciatica

Abstract: Transligamentous extension of herniated disc materials through the ruptured PLL is more important to its reduction in size than is the initial size of the herniated disc. Decrease in herniation ratio of more than 20% seems to correspond to successful clinical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
1
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(66 citation statements)
references
References 20 publications
2
57
1
4
Order By: Relevance
“…Significant reduction of symptoms in conservatively followed patients is seen in the long term (16)(17)(18). Comparing the conservative and surgical treatments for LDHR patients, there is no superiority of surgery over long-term conservative treatment (22).…”
Section: Discussionmentioning
confidence: 99%
“…Significant reduction of symptoms in conservatively followed patients is seen in the long term (16)(17)(18). Comparing the conservative and surgical treatments for LDHR patients, there is no superiority of surgery over long-term conservative treatment (22).…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous regression as a result of enzymatic degradation is one of the hypothesis, the others are based on the retraction of the disc into the intervertebral space, and on the concept of dehydration with loss of water content of the herniated disc material. Many authors reported various characteristics of the herniations like factors related to the resorption process as penetration through the posterior longitudinal ligament (PLL), size of herniation, and existence of cartilage and anulus fi brosus tissue in the herniated material (13)(14)(15)(16). Migrating and extruding type herniations have a higher tendency to decrease in size in followup studies (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…Many authors reported various characteristics of the herniations like factors related to the resorption process as penetration through the posterior longitudinal ligament (PLL), size of herniation, and existence of cartilage and anulus fi brosus tissue in the herniated material (13)(14)(15)(16). Migrating and extruding type herniations have a higher tendency to decrease in size in followup studies (13,14). Larger migrating type herniations demonstrate the greatest degree of resorption, so they regress more rapidly than smaller ones.…”
Section: Discussionmentioning
confidence: 99%
“…12 It is also recognised that greater resorption of herniated discs occurs when there is a sequestered fragment. 13,14 It is possible that this phenomenon of disappearing discs occurs more frequently. These cases are probably not detected because few patients have MRI examinations after the resolution of their symptoms.…”
Section: British Journal Of General Practice September 2008mentioning
confidence: 99%